TELAAH PEMIKIRAN MUHAMMAD NAQUIB AL-ATTAS DAN RELEVANSINYA DALAM PEMBENTUKAN KARAKTER MELALUI KURIKULUM MERDEKA - Jayanti, Suci; S, Zulkarnain; Ismail (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
This study aims to describe and analyze Muhammad Naquib Al-Attas' educational thoughts on the Merdeka Curriculum in Indonesia. The research method used is a qualitative approach to the type of library research. Data collection was carried out by reviewing documents, namely books and research journals on the educational thoughts of Muhammad Naquib Al-Attas and the Merdeka Curriculum, while the data analysis technique used content analysis. The results of the study show that Muhammad Naquib Al-Attas's educational thinking refers to the term ta'dib which is rooted in the word adab which means coaching that is specific to humans that is oriented not just to physical and material activities but to the participation of psychic and immaterial activities. Forms of educational thought of Muhammad Naquib Al-Attas namely the purpose of education to create good human beings, the distribution of fardu 'ain and fardu kifayah curriculum, and Islamic education methods, namely the method of monotheism as well as metaphors and stories. Muhammad Naquib Al-Attas's thoughts are relevant to the objectives of the Free Learning Curriculum in Character Formation through the P5 learning system to form students with Pancasila character. As for the first Pancasila, the YME Godhead underlies the other precepts so that it has the goal of forming good human beings.